Study on the irrigation water distribution system developed by Barind Multipurpose Development Authority - Rahman, Md. Mosiur; Kamal, A.H.M.; Al Mamun, Abdullah; Miah, Md. Shafi Uddin (Journal of the Bangladesh Association of Young Researchers, 2012)
Irrigated agriculture has been playing a vital role for the growth in crop production in Bangladesh. Minor irrigation comprising of shallow tubewells (STWs), deep tubewells (DTWs), hand tubewells (HTWs) and low-lift pumps (LLPs) is a major irrigation system in the country. Poor performance of irrigation is an issue for the expansion of irrigated area. The present study was carried out to examine the conveyance efficiency and rate of irrigation water loss in DTW schemes in Bogra, Thakurgaon and Godagari zones of Barind Management Development Authority. There were various types of water distribution identified in these schemes with including Poly Venyl Chloride (PVC) buried pipe, cement concrete (CC) rectangular, Ferro trapezoidal, Ferro semicircular and rectangular earth drain. The average conveyance efficiency of PVC buried pipe for Bogra, Thakurgaon and Godagari zones ranged from 94.46% to 95.37% and rate of water loss ranged from 5.45% to 9.55% in three study zones. Average conveyance efficiency of CC rectangular for Bogra and Godagari zone ranged from 91.20% and rate of water loss from 6.58% to 9.93%. Average conveyance efficiency of Ferro trapezoid for Bogra and Godagari zone ranged from 87.80% to 90.06% and rate of water loss ranged from 9.94% to 12.21%. Average conveyance efficiency of Ferro semicircle for Bogra and Godagari zone ranged between 88.13% and 86.82% and rate of water loss between 11.59% and 11.68%. Average conveyance efficiency and rate of water loss of rectangular earth drain Godagari zone was 58.66% and 42.29% respectively. About 80% farmers recommended buried pipe irrigation system and about 20% semi-circular channel. The study suggests that the improved water distribution system as developed by BMDA is sustainable to increase productivity of irrigation systems in Bangladesh. DOI: http://dx.doi.org/10.3329/jbayr.v1i2.10032